2020
DOI: 10.1063/1.5140599
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of x-ray irradiation on charge transport and charge collection efficiency in stabilized a-Se photoconductors

Abstract: Stabilized amorphous selenium (a-Se) photoconductive layers are currently used in the majority of modern digital x-ray flat panel imaging detectors in mammography. We examine the effects of pre-exposure of a-Se to high-dose x-ray irradiation on both hole and electron lifetimes, τe and τh, respectively, without any field applied to the device. The x-ray irradiation was from an Al-filtered tungsten target x-ray tube. We show that reduction in τh and τe depends only on the total or accumulated dose, D, absorbed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Finally, it is useful to comment on the effect of the absorbed radiation on the charge carrier ranges in a-Se. As shown previously [ 24 ], the irradiation of a-Se with X-rays generates deep hole traps and hence shortens the hole lifetime and the range, while the electron transport seems to remain relatively unaffected. The present work assumes that there are no X-ray-generated deep traps in the sample, that is, the sample has been rested for a sufficient period of time for X-ray-induced defects to anneal out.…”
Section: Resultssupporting
confidence: 61%
“…Finally, it is useful to comment on the effect of the absorbed radiation on the charge carrier ranges in a-Se. As shown previously [ 24 ], the irradiation of a-Se with X-rays generates deep hole traps and hence shortens the hole lifetime and the range, while the electron transport seems to remain relatively unaffected. The present work assumes that there are no X-ray-generated deep traps in the sample, that is, the sample has been rested for a sufficient period of time for X-ray-induced defects to anneal out.…”
Section: Resultssupporting
confidence: 61%
“…The films were of electronic device quality and equivalent to the i-layer in a typical p-i-n-type a-Se X-ray detector structure. Charge transport and trapping in films of nearly identical composition and preparation conditions have been already extensively reported [41][42][43], and will not be repeated here, though parameters determined from similar time-of-flight transient photoconductivity measurements as in the latter references were used in the modelling the section below.…”
Section: Methodsmentioning
confidence: 99%
“…(b) There is a need to understand the dependence (if any) of W i and F on the total dose and the dose rate at different temperatures. (c) Recent work has shown that x-ray-generated defects in a-Se depend on the total x-ray dose and not on the dose rate [150]. Most importantly, the x-ray-induced damage was not permanent, and the a-Se structure recovered back to its original state.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 98%